2020
DOI: 10.1186/s42787-020-0069-y
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate general exponential models with stress-strength reliability application

Abstract: In this paper, we introduce two families of general bivariate distributions. We refer to these families as general bivariate exponential family and general bivariate inverse exponential family. Many bivariate distributions in the literature are members of the proposed families. Some properties of the proposed families are discussed, as well as a characterization associated with the stress-strength reliability parameter, R, is presented. Concerning R, the maximum likelihood estimators and a simple estimator wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Many authors explore the stress-strength model for different probability distributions. For example, Khames and Mokhlis [19] introduced a bivariate general exponential model for the stress-strength reliability model. Saber et al [18] suggested a remained stress-strength model for the generalized exponential model.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors explore the stress-strength model for different probability distributions. For example, Khames and Mokhlis [19] introduced a bivariate general exponential model for the stress-strength reliability model. Saber et al [18] suggested a remained stress-strength model for the generalized exponential model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Refs. 9,1517 established the stress-strength models with exponential bivariate distributions. However, the main emphasis of this research is to investigate the system reliability in which the components follow exponential bivariate distributions.…”
Section: Introductionmentioning
confidence: 99%